Gen Z's Perception of Marriage and the Reasons Behind It Waithood Case Study: Subdistrict Hero, District North Binjai, Binjai City - Putri Nabilla; Suci Ramadhona (SEAN Institute, 2025)
Study This aim For explore meaning marriage and reasons postpone wedding according to Generation Z in Heroes Subdistrict North Binjai . Generation Z born in 1997 – 2012. Focus main study This is For understand view Generation Z against marriage and Through interview deep , found that Generation Z views wedding as matter Which very important However No A little from they still postpone wedding Because a number of factors . Research This aim For identify perception Gene Z to institutions wedding And dig factors Which background decision For postpone wedding among them factor economic factors education and factors social . With approach qualitative descriptive study This involving interview deep to respondents aged 20-28 years who live in the sub-district hero subdistrict Binjai north . Research results show that part big respondents own view critical to marriage . They No Again look at wedding as objective main in life , but as something choice Which nature personal and contextual . The main reasons put forward For postpone wedding covers concern will stability economy , education and career that you want achieved , as well as expectation high social in wedding .